Exploring the Effects of EFL Classroom Management Strategies on Students’ Engagement and Academic Success: A Comprehensive Review - Esraful Haque Piyal; Md. Mehedi Hasan (Yayasan Visi Intan Permata, 2025)
settings where diverse learners and developing educational technologies present unique challenges. The review examines strategies for managing classrooms to enhance student engagement and academic performance, focusing on private universities in Bangladesh. Following the guidelines from Braun and Clarke (2006), 63 peer-reviewed studies were systematically analyzed thematically and were found through academic databases (e.g., Scopus, Google Scholar, ERIC, JSTOR, Education Source) published during the period 2015-2025. Developed themes included the instructing and managing behavior, the transformational possibilities of technology, as well as the significance of teacher self-efficacy and emotion. Findings suggest that successful classroom management requires sensitive approaches, with the fragmentation of traditional face-to-face interactions with digital tools, while addressing cultural and linguistic diversity. Long-term impacts remain underexplored, particularly regarding the growth of large classes and the integration of emotional intelligence into teacher training programs. The implications extend to educators, policymakers, and researchers, advocating for flexible frameworks that prioritize inclusivity, proven practices, and continuous professional development. Future research should adopt mixed-methods designs to evaluate the sustainability of these strategies over time.